Tinea Incognito—A Great Physician Pitfall - Julia Nowowiejska; Anna Baran; Iwona Flisiak (Journal of Fungi, 2022)
Tinea incognito is a dermatophyte infection exacerbated after inadequate administration of topical or systemic glucocorticoids. A 57-year-old man presented to the Department of Dermatology due to skin lesions persisting for one month. He reported having recently worked under hot conditions, in tight clothing, which caused sweating. Later, he noticed erythematous–exfoliative lesions in his groins and on the buttocks. He presented to the general practitioner who diagnosed him with eczema and prescribed clobetasole ointment. Since the skin lesions became more severe, he presented to the Department of Dermatology. On the physical examination, extensive erythematous–infiltrative lesions were observed in the area of medial, lateral, and posterior surface of both thighs and buttocks. Pustules were also present. Suspicion of tinea incognito was raised, and direct mycological examination and culture confirmed the presence of dermatophytes. The patient was prescribed topical terbinafine and oral itraconazole. Tinea incognito may be challenging to diagnose because the clinical presentation is relatively nonspecific and definitive culture or histopathological diagnosis such as by microscopic sample examination to identify fungal elements is not universally available. Every doctor has to keep in mind the fact that tinea may be a great mimicker of other dermatoses and to not prescribe medications without microscopic confirmation of tinea, and refer patients for dermatological consultation in case of doubt.